Germinoma recurrence in the conus medullaris 12 years after remission of primary intracranial lesion in the pituitary. (March 2016) - Sivasubramaniam, Vinothan; Zebian, Bassel; Thakur, Bhaskar; Saran, Frank; Chandler, Christopher
Highlights: Rare conus recurrence 12 years after complete remission of pituitary germinoma. First case of delayed spinal recurrence at a rare and distant site from the primary. Highlights need for long-term follow-up to limit disability from late recurrences. Further research into identifying patients at high risk of recurrences is required. Abstract: Intracranial germinomas are rare primary central nervous system tumours that are highly sensitive to radiotherapy and chemotherapy. Recurrences are infrequent, with the majority occurring within 5 years. Although multidisciplinary treatments have resulted in good event-free survival, long-term outcomes, over decades, are relatively poorly reported. We present a rare case of a recurrence in the conus medullaris 12 years after complete remission of the primary pituitary germinoma. To the best of our knowledge, this represents the first case of a significantly delayed spinal recurrence, occurring at a very distant and uncommon site, from the primary tumour. This case highlights the importance of long-term follow-up, even after complete remission, in order to identify and limit disability from late spinal recurrences in a relatively young patient population. We consider the literature regarding identifying high risk patients, and the role of craniospinal irradiation in limiting late spinal recurrences.